Peran tenaga kesehatan puskesmas sebagai komunikator dalam program indonesia sehat dengan pendekatan keluarga - Rachmawati, Tine Silvana (Jurnal Komunikasi Profesional, 2020)
This study discusses the role of Puskesmas medical professionals as communicators in implementation of Indonesia Sehat program with a family approach. Indonesia Sehat program is one of the government programs to improve quality of life of Indonesian people, which is part of the 5th agenda of the Nawa Cita program. In implementing the program, good communication skills of Puskesmas medical professionals is needed to explain the health status and nutritional status of the Indonesian people. The purpose of this study was to find the important role of communication skills for Puskesmas medical professionals and the effectiveness of interpersonal communication in the family approach undertaken by Puskesmas medical professionals. The method used in this research is qualitative with a case study approach. The results of this study show that Puskesmas medical professionals should not treat their patients as clients in business matters, they must treat them with empathy and compassion by conducting good and effective communication for better health.Â Keywords: Communicator; family approach; Indonesia sehat; Puskesmas medical professionals.